2020
DOI: 10.5964/ejop.v16i3.2213
|View full text |Cite
|
Sign up to set email alerts
|

Comparing theoretical models for the understanding of health-risk behaviour: Towards an integrative model of adolescent alcohol consumption

Abstract: The aim of the present manuscript is to test and compare the theory of reasoned action (TRA), theory of planned behaviour (TPB) and prototype-willingness model (PWM) in predicting risky alcohol consumption among adolescents and to build an integrative model to get a more comprehensive understanding of such risky behaviour. A total sample of 518 adolescents (55% females; 13-19 aged) recruited from Italian schools (7th to 12th grade) participated in a cross-sectional research study and completed an online questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 77 publications
1
7
0
2
Order By: Relevance
“…AUDIT-C uses a 5-point Likert scale, resulting in an overall score ranging from 0 to 12: scores of 0 were defined as current abstainers; scores <3 are consistent with non-atrisk alcohol consumption, thus moderate-drinkers scored 1-2 (females) and 1-3 (males); binge-drinkers were defined as AUDIT-C scores of ≥3 (females) and ≥4 (males). Previous studies have confirmed internal consistency α = 0.75 (31).…”
Section: Alcohol Use Disorder Identification Test-consumptionmentioning
confidence: 62%
“…AUDIT-C uses a 5-point Likert scale, resulting in an overall score ranging from 0 to 12: scores of 0 were defined as current abstainers; scores <3 are consistent with non-atrisk alcohol consumption, thus moderate-drinkers scored 1-2 (females) and 1-3 (males); binge-drinkers were defined as AUDIT-C scores of ≥3 (females) and ≥4 (males). Previous studies have confirmed internal consistency α = 0.75 (31).…”
Section: Alcohol Use Disorder Identification Test-consumptionmentioning
confidence: 62%
“…The paper contributed by Andrea Caputo (“Comparing theoretical models for the understanding of health-risk behavior: Towards an integrative model of adolescent alcohol consumption”) applied the TPB in combination with the prototype-willingness model (PWM) to predict risky alcohol consumption among adolescents ( Caputo, 2020 ). In essence, PWM considers prototype favourability and similarity as an additional behavioral antecedent.…”
Section: Applications In Public Health and Political Sciencementioning
confidence: 99%
“…Subjective norm is defined as the perceived external social pressure or expectation of a particular group of people or society to perform certain behaviors (Fishbein and Ajzen, 1975;Ajzen, 1991;Ajzen and Fishbein, 2000). Subjective norms are the best predictor of a person's behavior (Caputo, 2020;La Barbera and Ajzen, 2020). Several studies have demonstrated a positive relationship between subjective norms and household energysaving intention (Hori et al, 2013;Chen et al, 2017;Wang et al, 2018a;Ding et al, 2019;Mansor and Sheau-Tingi, 2019;Nie et al, 2019;Hien and Chi, 2020).…”
Section: Theoretical Basismentioning
confidence: 99%
“…The more positive person's attitude towards a behavior, the more likely that person intends to perform a behavior (Ajzen, 1991). Attitude is a significant factor related to an individual's intention to perform a behavior (Verplanken and Orbell, 2003;Bosnjak et al, 2020;Caputo, 2020). Recent studies have shown that an energy-saving attitude positively affects household energy-saving intention (Zhang et al, 2014;Chen et al, 2017;Wang et al, 2018a;Ding et al, 2019;Mansor and Sheau-Tingi, 2019;Nie et al, 2019;Hien and Chi, 2020).…”
Section: Relationship Between Attitude and The Intention To Save Energymentioning
confidence: 99%